INFLUENCE OF SOCIAL SUPPORT NETWORKS FOR ADOLESCENT BREASTFEEDING MOTHERS IN THE PROCESS OF BREASTFEEDING - Verônica de Azevedo Mazza; Regina Célia Tanaka Nunes; Rafaela Zilli Palmeiro Tararthuch; Ana Maria Cosvoski Alexandre; Jaqueline Vicentin Patel (Universidade Federal do Paraná, 2014)
The aim was to investigate the influence of the social support networks on the process of breast-feeding among adolescent mothers who are breast-feeding. This is an exploratory study with a qualitative approach undertaken in a municipality in the metropolitan region of Curitiba, in three Health Centers with Family Health Strategy, in the period September - October 2011. Nine adolescents were interviewed using semi-structured interviews, and the data were analyzed using thematic categorical analysis. Two categories were listed: Influence of the Primary Social Support Network, and Influence of the Secondary Social Support Network. The Primary Network is characterized by family members and close persons, with special participation from the women. The health institutions and professionals make up the secondary network, which is directed towards health education and encouragement for the practice of breast-feeding. The interaction between the professionals, the breast-feeding mother and her family is important, as it leads to more efficacious actions for the promotion of breast-feeding, in accordance with the context.